Stars in forbidden triples generating a finite set of graphs with minimum degree four - Kotani, Takafumi (GTA Research Group, Univ. Newcastle, Indonesian Combinatorics Society and ITB, 2025)
For a family H of graphs, a graph G is said to be H-free if G contains no member of H as a induced subgraph. Let G4(H) denote the family of connected H-free graphs having minimum degree at least 4. In this paper, we characterize the families H of connected graphs with |H|=3 such that H contains a star and G4(H) is a finite family, except for the case where K4, K1, n⊆H with 3 ≤ n ≤ 4.